2016
DOI: 10.21037/jtd.2016.03.38
|View full text |Cite
|
Sign up to set email alerts
|

Severe adenovirus community-acquired pneumonia in immunocompetent adults: chest radiographic and CT findings

Abstract: Background: Severe adenovirus pneumonia and its associated imaging features are well-described in immunocompromised patients but are rare and poorly understood in immunocompetent adults. We sought to describe the radiographic and CT findings of severe adenovirus community-acquired pneumonia (CAP) in eight immunocompetent adults. Methods: We reviewed systematically chest imaging manifestations of laboratory-confirmed severe adenovirus pneumonia in eight immunocompetent adults from April 2012 to April 2014. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
5
18
0
1
Order By: Relevance
“…Interestingly, in our study CAP radiological features were not affected by the presence of VRTI. This is consistent with observations that, in some instance, viral and bacterial pneumonia may have similar radiological features [34] It is worth noting that, in spite of higher PSI scores in presence of VRTIs, we found no association between VRTIs and need of antibiotic treatment escalation, ICU admission and risk of mortality. Other studies investigating clinical outcomes in the same setting found opposite results.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in our study CAP radiological features were not affected by the presence of VRTI. This is consistent with observations that, in some instance, viral and bacterial pneumonia may have similar radiological features [34] It is worth noting that, in spite of higher PSI scores in presence of VRTIs, we found no association between VRTIs and need of antibiotic treatment escalation, ICU admission and risk of mortality. Other studies investigating clinical outcomes in the same setting found opposite results.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, focal or subsegmental consolidation was more frequent in patients without mechanical ventilation, while patients with mechanical ventilation commonly indicated initial predominant lung consolidation or progress rapidly from initial focal consolidation to lobar consolidation, suggesting that patients required mechanical ventilation may be more prone to indicate intra-pulmonary abnormalities in CT scans. Consistent with previous studies [13,21] , 60% of this group of cases demonstrated pleural effusion and 20% of patients indicated pericardial effusion, which may be related to more serious abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Yao et al [12] reported Human adenovirus among hospitalized children was detected in every month throughout the study period from April 2017 to March 2018, peaking in August 2017. In current study, summer and winter were peak season of immunocompetent adult adenovirus pneumonia, which was partially similar with another study that reported seasonal peak for adenovirus infections in winter and spring in immunocompetent patients [13] .…”
Section: Discussionsupporting
confidence: 91%
“…Adenoviral pneumonia in immunocompetent individuals presents with chest Computerized Tomographic (CT) scan findings of subpleural and peribronchovascular consolidation with or without surrounding ground glass opacities [ 36 , 37 ]. A single center study done in a tertiary care hospital in Korea in 2016 suggested that large parenchymal involvement and presence of pleural effusion on CT are factors suggestive of progression to ARDS [ 38 ].…”
Section: Disease Spectrummentioning
confidence: 99%